117k views
5 votes
Please solve this question fast.

Please solve this question fast.-example-1

1 Answer

2 votes

Answer:

See Explanation

Explanation:


{a} = {6}^(x), \: \: b = {6}^(y) ...(given) \\ {a}^(y). {b}^(x) = 36..(1) \\ pluggig \: the \: values \: of \: a \: and \: b \: in \: (1) \\ ({6}^(x)) ^(y) . ({6}^(y)) ^(x) = {6}^(2) \\ {6}^(xy).{6}^(xy) = {6}^(2) \\ {6}^(xy + xy) = {6}^(2) \\ {6}^(2xy) = {6}^(2) \\ bases \: are \: equal \: so \: exponentes \: will \: also \: be\\ \: equal \\ \therefore \: 2xy = 2 \\ xy = (2)/(2) \\ \huge \red { \boxed{ xy = 1}} \\ hence \: proved \\

User The Thonnu
by
5.5k points